The effect of messaging on the acceptance of swaps to reduce the energy content of snacks and non-alcoholic drinks ordered in an experimental online workplace canteen: A randomised controlled trial. (1st July 2021) - Breathnach, S.; Koutoukidis, D.A.; Lally, P.; Boniface, D.; Sutherland, A.; Llewellyn, C.H.
Abstract: Finding effective ways to increase acceptance of lower-energy swaps offered for snacks and non-alcoholic drinks may reduce population energy intake. We examined whether incrementally increasing the tangibility of information accompanying swaps offered increased their acceptance. UK adults (n = 3481) selected a sweet snack, a savoury snack, and a drink in an experimental online canteen after being equally randomised to receive one of four messages when swaps were offered; a control message providing no specific information, a vague calorie message, an exact numeric-calories message or, a physical activity calorie equivalent (PACE). Primary outcomes were the between-group differences in (i) the odds that a sweet, savoury, or drink swap would be accepted and (ii) the energy content for each type of item ordered. Compared with control, the numeric-calories and PACE messages significantly increased the odds of accepting a sweet snack swap. All interventions significantly increased the odds of accepting savoury swaps compared with control. Only the PACE message significantly increased the odds of drink swap acceptance. The numeric-calories and PACE messages significantly reduced the energy content of sweet snacks. All interventions significantly reduced the energy content of savoury snacks. None of the intervention messages significantly reduced the energy content of drinks compared with control. Increasing the tangibility of information provided when offering swaps increased swap acceptance. PACE messaging was the most promising.